Hypoxia and fatigue impair rapid torque development of knee extensors in elite alpine skiers - Alhammoud, M.; Morel, B.; Girard, O.; Sevrez, V.; Germain, A.; Chamu, T.; Racinais, S.; Hautier, C. (Frontiers in Physiology, 2018)
This study examined the effects of acute hypoxia on maximal and explosive torque and fatigability in knee extensors of skiers. Twenty-two elite male alpine skiers performed 35 maximal, repeated isokinetic knee extensions at 180°·s-1 (total exercise duration 61.25 s) in normoxia (NOR, FiO2 0.21) and normobaric hypoxia (HYP, FiO2 0.13) in a randomized, single-blind design. Peak torque and rate of torque development (RTD) from 0 to 100 ms and associated Vastus Lateralis peak EMG activity and rate of EMG rise (RER) were determined for each contraction. Relative changes in deoxyhemoglobin concentration of the VL muscle were monitored by near-infrared spectroscopy. Peak torque and peak EMG activity did not differ between conditions and decreased similarly with fatigue (p<0.001), with peak torque decreasing continuously but EMG activity decreasing significantly after 30 contractions only. Compared to NOR, RTD and RER values were lower in HYP during the first 12 and 9 contractions respectively (both p<0.05). Deoxyhemoglobin concentration during the last five contractions was higher in HYP than NOR (p=0.050) but the delta between maximal and minimal deoxyhemoglobin for each contraction was similar in HYP and NOR suggesting a similar muscle O2 utilization. Post exercise heart rate (138±24 bpm) and blood lactate concentration (5.8±3.1 mmol.l-1) did not differ between conditions. Arterial oxygen saturation was significantly lower (84±4 vs. 98±1%, p<0.001) and ratings of perceived exertion higher (6±1 vs. 5±1, p<0.001) in HYP than NOR. In summary, hypoxia limits RTD via a decrease in neural drive in elite alpine skiers undertaking maximal repeated isokinetic knee extensions, but the effect of hypoxic exposure is negated as fatigue develops. Isokinetic testing protocols for elite alpine skiers should incorporate RTD and rate of EMG rise measurements as they display a higher sensitivity than peak torque and EMG activity.